MicroRNA-375 as a potential serum biomarker for the diagnosis, prognosis, and chemosensitivity prediction of osteosarcoma - Liu, Wei (J Int Med Res, 2017)
OBJECTIVE: This study was performed to examine serum microRNA-375 (miR-375) expression in patients with osteosarcoma and determine its diagnostic and prognostic value. METHODS: Serum samples were obtained from 95 patients with osteosarcoma and 95 healthy individuals. miR-375 expression was detected by real-time polymerase chain reaction. The associations of serum miR-375 expression with the patients’ clinicopathological characteristics and prognosis were then evaluated. Receiver operating characteristic curve analysis was performed to obtain the potential value of serum miR-375 as a biomarker for osteosarcoma diagnosis and chemosensitivity prediction. RESULTS: Serum miR-375 expression was significantly lower in patients with osteosarcoma than in healthy individuals. Low serum miR-375 levels were associated with advanced clinical stages, large tumor size, positive distant metastasis, and poor tumor response to preoperative chemotherapy. Receiver operating characteristic curve analysis illustrated that serum miR-375 could distinguish patients with osteosarcoma from healthy individuals and distinguish patients with a good pathologic response from those with a poor response. Multivariate analysis confirmed low serum miR-375 expression as a statistically significant independent unfavorable prognostic factor. CONCLUSIONS: Serum miR-375 expression was downregulated in patients with osteosarcoma and might serve as a biomarker for its diagnosis, prognosis, and chemosensitivity prediction.